PENGARUH MATA KULIAH PERENCANAAN PEMBELAJARAN TERHADAP KEMAMPUAN PEMBUATAN RPP K13 - Sundahry Sundahry (Jurnal Muara Pendidikan, 2021)
The purpose of this study was to see if there was an influence between the lesson planning courses on the ability to make lesson plans for undergraduate students at PGSD STKIP-MB for the academic year 2020/2021. The method used in this studi is a correlational type with a quantitative approach, with data collection techniques through questionnaires and documentation. The population in this study were all students who had taken lesson planning courses. The sample in this study uses saturated sapling, meaning that all members of the population 33 people are used as samples. The results showed that there was an influence between the lesson planning courses on the ability to make lesson plans, which resulted from the correction index value that had been obtained r was 0.653 (moderate of sufficient) from the results of hypothesis testing the value of tcount (0.463) > ttable (0.163), and because the value of tcount is greater that the value of ttable, H0 was rejected and Ha was accepted. In other words, there was an influence between lesson planning courses on the ability to make lesson plans.